DIDACTIC POTENTIAL OF YOUTUBE CHANNELS FOR ENHANCED ENGLISH LANGUAGE LEARNING IN NON-LINGUISTIC PROGRAMS - Blynova, Neliia; Medynska, Svitlana; Voloboieva, Anna (Visnyk universytetu imeni Alʹfreda Nobeli͡a︡. Serii͡a︡: Pedahohika i psikholohii͡a, 2024)
The article is devoted to the didactic potential of English-language YouTube vlogs for learning English as a foreign language by students of non-philology programs. Modern teachers of foreign languages, working in non-philological specializations, face the challenge of diversifying didactic materials. The emergence of Web 2.0, technological advancements, and the information age present a plethora of opportunities to facilitate engaging, efficient, and high-quality English language learning for both educators and students. The purpose of the article is to provide an in-depth analysis of English-language YouTube vlogs encompassing a diverse range of topics, intended for learners of various demographics, including age, gender, socioeconomic background, and English proficiency level. The study explores the potential of integrating these YouTube channels into classroom and independent learning activities for students enrolled in non-philological programs. Methodology. The research employed a multi-pronged approach. An analysis of existing literature on the research topic provided insights into the current state of mobile learning research, both domestically and internationally. A descriptive method enabled the researchers to synthesize the experiences gained during the exploratory phase. Finally, the synthesis of the gathered data facilitated the formulation and execution of the research concept. The study investigates the didactic potential of eleven YouTube channels for fostering English language learning (as a second foreign language) among students in non-philological programs. A selection of English-language vlogs has been analysed, encompassing categories such as everyday life (The Cottage Fairy), education (Lindie Botes, Ruri Ohama, RealLife English), culinary arts (Delish), popular science, (Geography Now, Smarter Every Day, Vsauce, Thomas Frank, Matt D’Avella), and culture and arts (Chris Stuckmann). These vlogs cater to a broad audience, varying in terms of age, English proficiency level, thematic focus, subscriber count, viewership statistics, and uploaded video content. The analysis revealed that the proposed materials can be seamlessly integrated into the learning process for first-year students categorized as elementary, pre-intermediate, and intermediate learners. A unifying characteristic across the examined YouTube channels is the “edutainment” concept. This approach emphasizes the achievement of educational objectives by combining a gamified learning experience with the instructional content itself. The sheer variety of English language learning vlogs empowers learners to select topics that align with their personal interests, preferred language complexity, and desired level of visual engagement. Additionally, the content offers valuable knowledge for overall development. For educators, the primary advantage of YouTube channels lies in their ability to illustrate key lesson topics with engaging video content delivered by native speakers or individuals who, like the students themselves, have learned English and can offer practical advice. Visual content ranks among the most effective pedagogical tools. Strategically chosen YouTube vlogs can significantly enhance students’ vocabulary development, facilitate the acquisition of idioms and colloquial speech patterns, improve pronunciation, strengthen linguistic competencies, and refine listening and speaking skills. Furthermore, the broad thematic range of the content contributes to an expanded worldview. Students gain exposure to diverse cultural aspects of other countries, acquire new knowledge about the world, develop effective time management skills, and glean a wealth of valuable and engaging information. Conclusion. The integration of English-language YouTube vlogs into the curriculum of non-philological programs presents a promising avenue for enriching the foreign language learning experience. The “edutainment” approach fosters a stimulating and interactive learning environment, catering to diverse learning styles and facilitating the acquisition of essential language skills and knowledge. Further research is necessary to explore the long-term efficacy of this approach and its impact on student learning outcomes.